View of the shrine rear decorated with the kirtimukhas (demon faces) and miniature decorative towers (aediculae). In each of these kirtimukhas are placed a form of Rudra - Brig. Ajai Singh (2021)
Image courtesy: Brig A.P. Singh - www.collectingmoments.in